Graphene composite material as well as preparation method and application thereof
Through the preparation of graphene composite materials, the graphene conductivity and polyhedral structure buffer volume expansion are used to solve the problem of low performance of sodium ion batteries, and the rate performance and cycle stability are significantly improved.
Patent Information
- Application Number
- CN202510105430.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-03-18
AI Technical Summary
The capacity and rate performance of sodium ion batteries are low, mainly due to the slow kinetic process caused by the large radius of sodium ions and the problem of mismatch between cations and the anode material.
Using graphene composite material, a graphene composite material with CoSe2 loading was prepared by mixing cobalt-based metal organic frame material, graphene and organic solvent and selenizing. This method uses graphene conductivity and polyhedral structure to buffer volume expansion, prevent CoSe2 nanoparticles from aggregation and improve the exposure of active sites.
It significantly improves the conductivity and stability of composite materials, improves the rate performance and cycle stability of sodium ion batteries, and improves the overall performance of the battery.
Smart Images

Figure CN119650671A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium batteries, and in particular relates to a graphene composite material and a preparation method and application thereof. Background Art
[0002] People are inseparable from portable electronics in their daily lives. The rapid development of mobile phones, notebooks, and computers has driven the continuous innovation of lithium-ion battery technology. However, the shortage of lithium resources in the earth's crust has always been a problem that lithium batteries will face in the development of lithium batteries. For long-term development, it is necessary to develop other systems of secondary batteries. Sodium-ion batteries (SIBs) have attracted much attention from researchers due to their advantages such as abundant sodium resources and low prices.
[0003] The main factor restricting the development of sodium-ion batteries is the larger sodium ion radius of about 0.106nm, while the radius of lithium ions is only 0.076nm. The excessively large ion radius will lead to slow kinetics and mismatch between cations and anode materials, resulting in low capacity and rate performance of sodium-ion batteries.
[0004] CoSe 2 It has attracted much attention due to its high theoretical capacity and is considered a potential positive electrode material for SIBs. Compared with Co-O and Co-S bonds, Co-Se bonds are relatively weak and easy to break and reform, which is conducive to the occurrence of reactions. 2 The low conductivity and easy agglomeration during the preparation process will lead to insufficient contact between the electrolyte and the material, resulting in a slow kinetic process. In addition, the insertion / extraction of sodium ions will lead to the slowing of the CoSe 2 Severe volume expansion leads to poor cycling stability. Summary of the invention
[0005] The purpose of the present invention is to provide a graphene composite material and a preparation method and application thereof. The method provided by the present invention can further improve the conductivity and stability of the composite material.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a graphene composite material, comprising the following steps:
[0008] mixing a cobalt-based metal organic framework material, graphene and an organic solvent to obtain a precursor material;
[0009] The precursor material is subjected to selenization treatment to obtain the graphene composite material.
[0010] Preferably, the cobalt-based metal organic framework material includes ZIF-67, HOF-5, ZIF-9(Co) or CoBPDCA.
[0011] Preferably, the mass ratio of the cobalt-based metal organic framework material to graphene is 1 to 3:1.
[0012] Preferably, the organic solvent comprises ethanol or methanol;
[0013] The mixing method is ultrasound, and the ultrasound time is 10 to 20 minutes.
[0014] Preferably, the process of the selenization treatment is: placing a selenium source upstream of a tube furnace, placing the precursor material downstream of the tube furnace, and calcining under a protective atmosphere.
[0015] Preferably, the selenium source comprises selenium powder.
[0016] Preferably, the mass ratio of the selenium source to the precursor material is 3 to 7:1.
[0017] Preferably, the calcination temperature is 450-600°C and the holding time is 1-3h;
[0018] The heating rate to the calcination temperature is 2 to 10° C. / min.
[0019] The present invention also provides a graphene composite material prepared by the preparation method described in the above technical solution, comprising a graphene matrix and CoSe supported on the graphene matrix. 2 .
[0020] The present invention also provides the use of the graphene composite material described in the above technical solution as an electrode active material in a sodium ion battery.
[0021] The invention provides a method for preparing a graphene composite material, comprising the following steps: mixing a cobalt-based metal organic framework material, graphene and an organic solvent to obtain a precursor material; and performing selenization treatment on the precursor material to obtain the graphene composite material.
[0022] The present invention uses metal organic framework materials as templates and precursors to prepare CoSe with a polyhedral structure 2 , can buffer the Na + The volume expansion caused by embedding / ejection reduces the powdering degree of the electrode. At the same time, the flake-like wrinkled structure of graphene is used as a connection between each CoSe 2 Polyhedral matrix can prevent excessive CoSe 2The aggregation of nanoparticles is conducive to the exposure of active sites, and the excellent conductivity of graphene can enhance the conductivity of the composite material, thereby improving the rate performance and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 CoSe 2 Crystal structure model diagram;
[0024] Figure 2 XRD diagram of the graphene composite material obtained in Examples 1 to 3;
[0025] Figure 3 This is a SEM image of the graphene composite material obtained in Example 3;
[0026] Figure 4 TEM image of the graphene composite material obtained in Example 3;
[0027] Figure 5 HRTEM image of the transmission image of the graphene composite material obtained in Example 3;
[0028] Figure 6 The charge and discharge curve of the third cycle of the sodium battery assembled in Test Example 2 at a current density of 0.05C;
[0029] Figure 7 is the rate curve of the sodium battery assembled in Test Example 2;
[0030] Figure 8 is the cyclic voltammetry curve of the sodium battery in Test Example 2;
[0031] Fig. 9 is the cycle performance curve of the sodium battery in Test Example 2;
[0032] Fig.10 is the electrochemical impedance diagram of the sodium battery in Test Example 2;
[0033] Fig.11 The cyclic voltammograms of the sodium battery assembled with the graphene composite material obtained in Example 3 at different scan rates;
[0034] Fig.12 A curve showing the relationship between the scan rate and the peak current of the sodium battery assembled with the graphene composite material obtained in Example 3;
[0035] Fig.13 The contribution relationship between the diffusion control ability and capacitance of the sodium battery assembled with the graphene composite material obtained in Example 3;
[0036] Fig.14 CoSe 2The contribution relationship between the diffusion control ability and capacitance of the assembled sodium battery;
[0037] Fig.15 The contribution relationship between the diffusion control ability and capacitance of the sodium battery assembled with the graphene composite material obtained in Example 1. DETAILED DESCRIPTION
[0038] The present invention provides a method for preparing a graphene composite material, comprising the following steps:
[0039] mixing a cobalt-based metal organic framework material, graphene and an organic solvent to obtain a precursor material;
[0040] The precursor material is subjected to selenization treatment to obtain the graphene composite material.
[0041] The present invention mixes a cobalt-based metal organic framework material, graphene and an organic solvent to obtain a precursor material.
[0042] In the present invention, the cobalt-based metal organic framework material preferably includes ZIF-67, HOF-5, ZIF-9(Co) or CoBPDCA.
[0043] In the present invention, the ZIF-67 is preferably obtained by preparation, and the preparation method preferably comprises the following steps: dissolving dimethylimidazole and cobalt nitrate hexahydrate in methanol, and performing a coprecipitation reaction to obtain the ZIF-67.
[0044] In the present invention, the mass ratio of dimethylimidazole to cobalt nitrate hexahydrate is 328:249; the dosage ratio of dimethylimidazole to methanol is 328mg:20mL. In the present invention, the temperature of the coprecipitation reaction is preferably 25°C, and the time is preferably 24h. After the coprecipitation reaction, the present invention also preferably includes washing the obtained precipitate with ethanol and drying it, the number of ethanol washing is preferably three times, and the drying temperature is preferably 60°C.
[0045] In the present invention, the mass ratio of the cobalt-based metal organic framework material to graphene is preferably 1 to 3:1, specifically 1:1, 2:1, 3:1. In the present invention, the organic solvent preferably includes ethanol or methanol; the mixing method is preferably ultrasound, and the ultrasound time is preferably 10 to 20 minutes. After the mixing, the present invention also preferably includes drying the obtained mixed liquid.
[0046] After obtaining the precursor material, the present invention performs selenization treatment on the precursor material to obtain the graphene composite material.
[0047] In the present invention, the process of the selenization treatment is preferably: placing the selenium source upstream of the tube furnace, placing the precursor material downstream of the tube furnace, and calcining under a protective atmosphere.
[0048] In the present invention, the selenium source preferably includes selenium powder. In the present invention, the mass ratio of the selenium source and the precursor material is preferably 3 to 7:1, specifically 3:1, 5:1 or 7:1. In the present invention, the calcination temperature is preferably 450 to 600°C, specifically 450°C, 500°C, 550°C, 600°C; the holding time is preferably 1 to 3h, specifically 1h, 2h, 3h; the heating rate to the calcination temperature is preferably 2 to 10°C / min, specifically 2°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min. In the present invention, the protective atmosphere is preferably nitrogen. After the calcination, the present invention also preferably includes naturally cooling the obtained material to room temperature and grinding.
[0049] The present invention also provides a graphene composite material prepared by the preparation method described in the above technical solution, comprising a graphene matrix and CoSe supported on the graphene matrix. 2 In the present invention, the CoSe 2 The loading mass percentage on the graphene composite material is preferably 50 to 75%.
[0050] The present invention also provides the use of the graphene composite material described in the above technical solution as an electrode active material in a sodium ion battery.
[0051] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0052] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] Example 1
[0054] 328 mg of dimethylimidazole and 249 mg of cobalt nitrate hexahydrate were dissolved in 20 mL of methanol, and the resulting mixed solution was co-precipitated at 25°C for 24 hours. The purple precipitate was then washed three times with ethanol and dried at 60°C to obtain ZIF-67;
[0055] The obtained ZIF-67 and graphene were ultrasonically compounded in an ethanol solution at a mass ratio of 1:1 for 0-20 minutes; after drying, the obtained precursor material and selenium powder were respectively placed in a tube furnace (wherein the mass ratio of selenium powder to precursor material was 3:1), the selenium powder was located upstream of the airflow, and the precursor material was located downstream of the airflow, and in an argon atmosphere, the temperature was increased from room temperature to 550°C at a heating rate of 5°C / min, and the temperature was kept for 2 hours, and then naturally cooled to room temperature and ground to obtain the graphene composite material (denoted as CoPG1), wherein CoSe 2 The loading mass percentage is 50%.
[0056] Example 2
[0057] A graphene composite material was prepared in the same manner as in Example 1, except that the mass ratio of ZIF-67 to graphene was 2:1. The obtained graphene composite material was denoted as CoPG2, CoSe 2 The loading mass percentage is 67%.
[0058] Example 3
[0059] A graphene composite material was prepared in the same manner as in Example 1, except that the mass ratio of ZIF-67 to graphene was 3:1. The obtained graphene composite material was denoted as CoPG3, CoSe 2 The loading mass percentage is 75%.
[0060] Performance Testing
[0061] Test Example 1
[0062] Figure 1 CoSe 2 The crystal structure model diagram, the lattice parameters a, b and c are 4.84, 7.72 and The purple balls are Co atoms and the yellow balls are Se atoms.
[0063] Figure 2 The XRD patterns of the graphene composite materials obtained in Examples 1 to 3 show that the cobalt diselenide of CoPG1, CoPG2 and CoPG3 is in orthorhombic phase (PDF card number: 53-0449), corresponding to (110), (011), (101), (111), (120), (200), (210), (211), (002), (130), (031), (221), (311), (310) and (122) crystal planes, respectively, indicating that the composited CoPG1, CoPG2 and CoPG3 have good crystallinity.
[0064] The ZIF-67 and graphene composite material obtained in Example 1 was further subjected to scanning electron image analysis, wherein Figure 3This is a SEM image of the graphene composite material obtained in Example 3. It can be seen that the wrinkled sheet structure is a graphene material, and the nanoparticles supported on the graphene are cobalt diselenide nanomaterials. The cobalt diselenide nanomaterials are embedded between the graphene layers.
[0065] Figure 4 This is a TEM image of the graphene composite material obtained in Example 3. It can be seen that the cobalt diselenide has a regular hexadecahedral porous structure; the diameter of the cobalt diselenide nanoparticles is about 500 nm, and the distribution is uneven, with more and thicker particles in the middle and relatively thin particles on both sides, and the hexadecahedral edges are clear.
[0066] Figure 5 This is a HRTEM image of the transmission image of the graphene composite material obtained in Example 3; it can be seen that the outermost thin layer is a graphene carbon layer structure, and the inner layer is a cobalt diselenide (101)(111)(031) crystal plane, with interplanar spacings of 0.296nm, 0.257nm, and 0.171nm, and the interplanar spacing data is consistent with the X-ray diffraction data.
[0067] Test Example 2
[0068] The graphene composite materials obtained in Examples 1 to 3 and CoSe 2 As electrode active materials, electrodes were prepared and assembled into sodium batteries for electrochemical performance testing;
[0069] Assembly process: The electrode active material, conductive graphite and carboxymethyl cellulose (CMC) are mixed and ground in a weight ratio of 7:1.5:1.5 (water is used as a dispersant). The above slurry is then applied to copper foil and vacuum dried at 60°C for 10 hours to finally obtain the electrode. The average mass of the electrode is about 0.8-1.0 mg / cm 2 ; Sodium sheet was used as the counter electrode, Celgard2400 microporous polypropylene membrane was used as the separator, and the electrolyte was 1M NaClO 4 (The solvent is ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), the volume ratio is 1:1:1, and 5% fluoroethylene carbonate (FEC) is added to assemble a sodium battery;
[0070] The electrochemical performance of the sodium battery obtained above was tested, and the performance curve obtained was as follows: Figures 6 to 12 As shown;
[0071] in Figure 6 The charge and discharge curve of the assembled sodium battery at the third cycle at a current density of 0.05C. Figure 6 It can be seen that at a current density of 0.05C, CoSe 2 Has the smallest specific capacitance, about 344mAh·g -1The specific capacitance of the composite CoPN1, CoPN2 and CoPN3 is significantly higher than that of the original CoSe 2 , 485, 276 and 565 mAh g -1 , which is due to the introduction of graphene greatly enhancing the CoSe 2 However, the specific capacitance of CoPN3 is significantly higher than that of CoPN1 and CoPN2, which proves that the content of graphene composite has a great influence on the specific capacitance, and the increase or decrease of graphene content does not guarantee the continuous increase or decrease of specific capacitance.
[0072] Figure 7 is the rate curve of sodium battery, from Figure 7 It can be seen from the data that at current densities of 0.05C, 0.2C, 0.5C, 1C and 2C, the capacity of CoPG3 is 565mAh·g -1 , 507mAh·g -1 , 485mAh·g -1 , 448mAh·g -1 and 376mAh·g -1 At a current density of 5C, CoPG3 can also reach 154mAh·g -1 The specific capacity of CoPG1 is only 27% at a current density of 0.05C. However, at a current density of 5C, it shows a capacity retention of 294 mAh g -1 The capacity of CoGP1 is about 60% of the capacity at 0.05C current density. When the current density increases, CoGP1 has a higher capacity retention rate than CoGP3, so the rate performance is better, which means that the rate performance and capacity of the composite material should be considered in practical applications.
[0073] Figure 8 The cyclic voltammetry curve of the sodium battery shows that CoSe 2 At 0.5mVs -1 The potential range is 0-3V at the scanning rate. In the third cycle of cyclic voltammetry curve, the curves before and after the composite graphene are the same. The electrode has three peaks in the cyclic voltammetry scan. This is due to the CoSe 2 In the anodic scan, there is a prominent peak at 1.95V, and a weak peak appears at about 1.6V on the left. This is due to the Na 2 CoSe formed by Se and metallic Co 2 It can be clearly observed from the comparison diagram that the peak currents of CoPN1, CoPN2 and CoPN3 are significantly higher than those of CoSe 2 , indicating that the composite material has better performance.
[0074] from Fig. 9 The cycle performance curve of sodium battery shows that CoSe 2 The cyclability of CoPG1, CoPG2 and CoPG3 at a current rate of 0.5C shows that after 100 cycles, the capacity retention rate of CoPG1 is 83.74%, the capacity retention rate of CoPG2 is 93.77%, and the capacity retention rate of CoPG3 is 87.07%, which is significantly higher than that of CoSe 2 (72.27%), the introduction of a small amount of graphene can effectively improve the stability of the material.
[0075] Fig.10 This is the electrochemical impedance diagram of the sodium battery. It can be seen that the original CoSe 2 In the high frequency region, there is a larger semicircle. The semicircles of the composite materials CoPG1, CoPG2 and CoPG3 are significantly smaller than those of CoSe. 2 , the smaller semicircle represents a smaller charge transfer resistance (Rct). The smaller charge transfer resistance makes the diffusion of electrolyte ions easier and faster, which makes it have better electrochemical kinetics, thereby improving the electrochemical performance of the electrode material. As can be seen from the image, the slope of CoPG3 is significantly lower than that of CoSe 2 Represents a faster ion diffusion process.
[0076] Fig.11 The cyclic voltammograms of the sodium battery assembled with the graphene composite material obtained in Example 3 at different scan rates show the cyclic voltammograms of CoPG3 at different scan rates from 0.5mV / s to 3mV / s, and the test explores the kinetic process of the material during the charge / discharge process. The proportion of capacitance control and diffusion control can be calculated according to formulas 1.1 and 1.2.
[0077] i=av b Formula 1.1
[0078] log i=b*log v+log a Formula 1.2
[0079] i is the peak current, v is the scan rate, where a and b are adjustable parameters. When the b value is close to 0.5, the diffusion control mechanism is dominant, while when the b value is equal to 1, it indicates that the capacitive behavior is dominant.
[0080] Fig.12 The curve of the relationship between the scan rate and the peak current of the sodium battery assembled with the graphene composite material obtained in Example 3, and the b values of the reduction peaks (1, 2 and 3) and the oxidation peak 4 are obtained by calculating the slope. The b values of the four peaks of CoPG3 are 0.881, 0.867, 0.850 and 0.764, respectively, which are all close to 1, indicating that the capacitive behavior is dominant.
[0081] In order to distinguish between capacitance and diffusion control in more detail, the contribution relationship between diffusion control ability and capacitance capacity of sodium batteries was tested at scan rates from 0.5 to 3 mV / s. Fig.13 The contribution relationship between the diffusion control ability and capacitance of the sodium battery assembled with the graphene composite material obtained in Example 3 is: Fig.14 CoSe 2 The contribution relationship between the diffusion control ability and capacitance of the assembled sodium battery, Fig.15 The contribution relationship between the diffusion control ability and capacitance of the sodium battery assembled with the graphene composite material obtained in Example 1;
[0082] from Fig.13 It can be seen that the dark part represents the capacitance contribution and the light part represents the diffusion control ability. It can be seen that at scan rates of 0.5, 1, 1.5, 2, 2.5 and 3 mV / s, the capacitive contribution of CoPG3 is approximately 74%, 79%, 83%, 86%, 87% and 86%, respectively, which is much greater than that of the original CoSe 2 Capacitive diffusion control 53% ( Fig.14 ), but is smaller than the capacitance diffusion control of CoPG1 ( Fig.15 ), which further explains why the rate performance of the composite material is better than that of the original CoSe 2 , and the rate performance of CoPG1 is better than that of CoPG3.
[0083] In summary, it can be seen that the graphene composite material provided by the present invention, through the introduction of graphene, makes CoSe 2 The aggregation of nano-polyhedrons is alleviated, allowing the active materials to better contact with the electrolyte ions and improve the utilization of active sites. CoPG3 can provide the maximum specific capacity of about 565 mAh g at 0.05C. -1 In addition, the introduction of graphene and the pore structure generated during the preparation process using the template method can effectively alleviate the Na + The volume expansion caused by the insertion and extraction process makes the electrode have better cycle stability as a whole. After 100 cycles at a rate of 0.5C, the capacity of CoPG1 maintains 93.77% of the initial capacity. 2 The composite ratio between nanostructured carbon and graphene represents the balance between capacity and rate, which provides an important reference for the design of electrode materials for sodium-ion batteries.
[0084] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a graphene composite material, characterized in that: The following steps are involved: mixing a cobalt-based metal organic framework material, graphene and an organic solvent to obtain a precursor material; The precursor material is subjected to selenization treatment to obtain the graphene composite material.
2. The preparation method according to claim 1, characterized in that: The cobalt-based metal organic framework material includes ZIF-67, HOF-5, ZIF-9 (Co) or CoBPDCA.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the cobalt-based metal organic framework material to graphene is 1 to 3:
1.
4. The preparation method according to claim 1, characterized in that: The organic solvent includes ethanol or methanol; The mixing method is ultrasound, and the ultrasound time is 10 to 20 minutes.
5. The preparation method according to claim 1, characterized in that: The process of the selenization treatment is: placing a selenium source upstream of a tube furnace, placing the precursor material downstream of the tube furnace, and calcining under a protective atmosphere.
6. The preparation method according to claim 5, characterized in that: The selenium source includes selenium powder.
7. The preparation method according to claim 5 or 6, characterized in that: The mass ratio of the selenium source to the precursor material is 3 to 7:
1.
8. The preparation method according to claim 7, characterized in that: The calcination temperature is 450-600°C and the holding time is 1-3h; The heating rate to the calcination temperature is 2 to 10° C. / min.
9. The graphene composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: It includes a graphene substrate and CoSe2 loaded on the graphene substrate.
10. Use of the graphene composite material according to claim 9 as an electrode active material in a sodium ion battery.